The Role of Competitiveness in Mediating the Influence of Customer Relationship Marketing on the Marketing Performance of Fitness Plus Indonesia Ubud Branch - SETYAWAN, I. G. N. Tomi; MARBUN, Saortua; DEWI, Luh Komang Candra (Journal of Tourism Economics and Policy, 2024)
This study aims to analyze the influence of customer relationship marketing on marketing performance, examine the impact of customer relationship marketing on competitiveness, explore the influence of competitiveness on marketing performance, and examine the role of competitiveness mediation in the relationship between customer relationship marketing and marketing performance. The sampling method used is accidental sampling. The population of this study consisted of 1,741 employees at Fitness Plus Indonesia Ubud Branch, with 95 people selected as respondents. The data used in this study is quantitative data, obtained from primary data sources. Data analysis was carried out using the Partial Least Square (PLS) approach with SmartPLS software version 3.2.7. The results of the study showed that: 1) customer relationship marketing had a positive and significant effect on marketing performance, 2) customer relationship marketing had a positive and significant effect on competitiveness, 3) competitiveness had a positive and significant effect on marketing performance, and 4) competitiveness was able to mediate the influence of customer relationship marketing on marketing performance.